Natural Products as Aromatase Inhibitors - Balunas, Marcy J. (2008)
With the clinical success of several synthetic aromatase inhibitors (AIs) in the treatment of postmenopausal estrogen receptor-positive breast cancer, researchers have also been investigating also the potential of natural products as AIs. Natural products from terrestrial and marine organisms provide a chemically diverse array of compounds not always available through current synthetic chemistry techniques. Natural products that have been used traditionally for nutritional or medicinal purposes (e.g., botanical dietary supplements) may also afford AIs with reduced side effects. A thorough review of the literature regarding natural product extracts and secondary metabolites of plant, microbial, and marine origin that have been shown to exhibit aromatase inhibitory activity is presented herein.